1990
DOI: 10.1161/01.str.21.12.1749
|View full text |Cite
|
Sign up to set email alerts
|

Sensory ataxic hemiparesis in thalamic hemorrhage.

Abstract: Ataxic hemiparesis with cerebellar-like features has been reported following infarction or hemorrhage of the thalamus. We describe five patients with incoordination and corticospinal tract signs in the limbs opposite a dorsolateral thalamic hemorrhage. In four patients the hemorrhage extended superiorly into the lateral ventricle, the adjacent paraventncular region, and the upper and medial parts of the posterior limb of the internal capsule. Instead of cerebellar dysfunction, these patients exhibited directio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 31 publications
(18 reference statements)
0
14
0
Order By: Relevance
“…Hyperesthetic ataxic hemiparesis was described in 8 cases, hyperesthetic hemiataxia was described in 24 cases, ataxic hemiparesis was described in 11 cases and sensory hemiataxia was described in 5 cases [14, 42, 46, 47, 50, 51, 54, 55, 58, 88, 102]. Isolated hemiataxia was described in 3 cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperesthetic ataxic hemiparesis was described in 8 cases, hyperesthetic hemiataxia was described in 24 cases, ataxic hemiparesis was described in 11 cases and sensory hemiataxia was described in 5 cases [14, 42, 46, 47, 50, 51, 54, 55, 58, 88, 102]. Isolated hemiataxia was described in 3 cases.…”
Section: Resultsmentioning
confidence: 99%
“…This is in contrast to the studies of Alarcon et al [3] and D’Olhaberriague et al [15], where chorea and hemichorea-hemiballismus were reported as the most common acute movement disorders respectively. Hemiataxia was described as ataxic hemiparesis, hypesthetic hemiataxia, hypesthetic ataxic hemiparesis or sensory hemiataxia [14, 41, 42, 46, 47, 50, 51, 54, 55, 58, 63]. Dobato et al [14] reported 5 patients with sensory ataxic hemiparesis following thalamic haemorrhage, where all patients had loss of deep sensations like joint and position sense.…”
Section: Discussionmentioning
confidence: 99%
“…There are frequently reported patients with subjective numbness, usually without sensory loss, and 1 patient 13 had accompanying pain without sensory loss. Review of the published cases reveal that also noted but not emphasized by the authors were 2 cases of contralateral Horner's syndrome, 14 ipsilateral facial hypesthesia, [15][16][17][18][19] and ipsilateral tongue deviation 8,19 -23 (presumably considered part of the hemiparesis). A more recent report of 2 patients, 17 1 with fleeting symptoms of weakness and corticospinal tract signs and the other with mild weakness, both accompanied by ataxia and prominent hemisensory loss was coined "hypesthetic-ataxic-hemiparesis" and likened to the DejerineRoussy (thalamic) syndrome.…”
Section: Gorman Et Al December 1998mentioning
confidence: 92%
“…Landau 25 asserts that some degree of clumsiness will be found in virtually any patient with hemiparesis and that it is nearly impossible to differentiate the 2 types of clumsiness clinically. Impaired position sense was thought to be the mechanism behind the ataxic component of the syndrome 14,26 in 5 patients 14 and was dubbed "sensory ataxic hemiparesis" (all of whom had thalamic lesions). Other reports 27 argue for cerebellar-type findings in patients with cortical infarction and postulate that the mechanism is intrinsic to the role of the lateral cerebellar hemisphere in integrating and communicating information from the cortical sensory association areas (superior parietal lobule) to the motor and premotor cortexes.…”
Section: Gorman Et Al December 1998mentioning
confidence: 99%
See 1 more Smart Citation